Determinación del desempeño físico-mecánico de vigas de concreto reforzado con la implementación de cementos terciarios con vidrio reciclado - Rojas-Calderón, Karyna (Instituto Tecnológico de Costa Rica, 2018)
This Project sought to find the mechanical-physifical properties acdquired by reinforced concrete beams with the inclusion of vitreous material, taking into account a study since the point of view of the material like hydraulic concrete, and evaluation of reinforced concrete elements designed and built to scale and capacity of the laboratory, subjecting them to flexion loads and evaluating different characteristics of the study. The vitreous material as a substitute for a percentage of the hydraulic cement of a hydraulic concrete mix, can behave as a water reducer, densifier and retarder of the acquisition of compresive strength, so it was sought to study holistically, from the point of view of gray material itself, even in composite elements (hydraulic concrete and reinforcing steel). All of the above in order to improve or achieve the typical behavior of different mixtures of hydraulic concrete (CAD 700 and high strength concrete of 400 kg / cm2), taking into account resistant behaviors, and electron scanning microscopy and diffractometry studies.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Concreto; Vigas de concreto; Propiedades físicas; Propiedades mecánicas; Resistencia; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture::Building engineering